IJIN LOKASI SEBAGAI PENGENDALI PERUBAHAN PENGGUNAAN TANAH PERTANIAN MENJADI NON PERTANIAN - Haryanto, Totok Dwinur (Universitas Slamet Riyadi, 2008)
Abstarct Population growth as a result of the development drive the need of land. Land then is not only related of agriculture. It is related to other usage to give other prosperity. To stop land usage shift to other non-agriculture purposes, it is necessary to regulate, to limit the shift. One of the ways is by regulating location premission. It is hoped that land usage shift to other purposes will not misused. Key words : location premition, land for non-agriculture